What if Sharia Weren’t the Enemy: Rethinking International Women’s Rights Advocacy on Islamic Law - Quraishi, Asifa (Columbia Journal of Gender and Law, 2011)
For many women’s rights activists working internationally, especially those coming from a western context, sharia is believed to be a major obstacle to women’s rights. In order to protect women from Muslim religious law, these advocates often position themselves aggressively against so-called sharia legislation and sharia in general. I believe that this approach is counterproductive and ultimately exacerbates, rather than improves, the situation for women living in Muslim-majority countries. In this article, I explain how current global feminist strategies have helped create an unwinnable and unnecessary war: that of sharia vs. women’s rights. Drawing on observations incident to my work on the zina (extra-marital sex) laws in Nigeria and Pakistan, I argue for an alternative: women’s rights advocates concerned about the situation of Muslim women around the world would do better not to mention Islamic law at all. This would be a major strategy shift, requiring significant restraint on the part of western secular feminist activists, but I believe it is worth it. I explain how, with this shift in approach, internationally-active women’s rights advocates might more effectively contribute to securing rights for women in Muslim-majority countries. This shift could also open up a new appreciation for a wider spectrum of feminism, including that coming from a sharia-mindful perspective. In short, I argue for a world of advocacy for women that is nuanced and sophisticated and works with—not against—the reality of sharia in Muslim lives.